Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

Peru: Social Issues and Comedy in Fiction - Cassano, Giuliana; Vásquez, Guillermo; Dettleff, James A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
The country’s political crisis led to the confrontation between the Peruvian Congress and President Martín Vizcarra on irreconcil- able limits. After a second denial of confidence, Vizcarra made use of his constitutional prerogatives and dissolved Congress at the end of September 2019. The majority of the mass media step in line with the different positions of the Executive or the opposition, giv- ing much more attention to the political situation, thus modifying the TV programing. In this scenario, the Enfoca group – owner of Latina station – has continued looking for potential buyers, but without success yet. The conglomerate – with interest in financial, health and productive sectors – does not feel that the investment made in acquiring all the station’s shares seven years ago yielded the expected results. Meanwhile, Willax – a small locally held station acquired by the Wong group in 2015 with promises of a large investment – has become a stronghold of opposition to the government of Vizcarra and the largest broadcaster of Korean fictions. In February 2020, they an- nounced that a commercial partnership had been signed with South Korean company CJ ENM, a production company of several Korean dramas and the award-winning film Parasite, but without indicating what this company could mean for audiovisual production in Peru.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Pérou (corpus analysé); Pérou (lieu de production du savoir); _Nettoyé

Colombia: Melodrama Lives in Times of Streaming - Díaz, Fernando Aranguren; Bohórquez, Borys Bustamante; Riveros Solórzano, Hernán Javier (Obitel 2020: Melodrama in Times of Streaming, 2020)
The year 2019 in Colombia was characterized by the presence of a series of social and cultural phenomena of high impact on the population, such as the National Strike on November 21, when dif- ferent sectors expressed their disagreement with the country’s poli- cies and the reforms that were being proposed for the new year. This situation led to a leading presence of the news on the small screen and, at the same time, an interesting reflection of national identity, the needs of various Colombian social groups and the cul- tural matrices of the nation. In this hectic context and in accordance with a certain global climate of crisis in democratic and government systems, a highly interesting television phenomenon emerges: the highly successful reappearance of the programs that marked differ- ent generations of compatriots and that, as in the past, once again led families to discuss episodes and situations presented under the classical structure of melodrama.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); Colombie (corpus analysé); Colombie (lieu de production du savoir); _Nettoyé

Brazil: Time of Brazilian Streaming - Vassallo de Lopes, Maria Immacolata; Prezia Lemos, Ligia (Obitel 2020: Melodrama in Times of Streaming, 2020)
In 2019, the World Wide Web (www) celebrated its 30th anni- versary, However, the internet had not yet asserted itself as a right in the “network society” (Castells, 2009), and its balance points to the expansion of both opportunities and threats. Another fact that deserves to be highlighted in the year was the drop in the rating as a global phenomenon that challenges the television industry. It means change of habits and search for new business models. The integration of platforms and the generation of quality content appear as pillars of thetransformation of audiovisual worldwide. And the changes are manifested with a certain degree of diversity, according to the economic and cultural characteristics of each society, with disruptive processes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Argentina: The Fall of Open TV Continues: Production Companies Bet on Platforms with Themes Regarding Marginality and Corruption - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
Serial fiction released in Argentina in 2019 continues to fall. Only one telenovela had more than 200 chapters. To a lesser extent than the previous year, the supply of serialized fiction incorporated themes from the social agenda, especially feminist struggles and the visibility of sexual dissidence. The channels found in the co-produc- tion and in the production for platforms one of the ways in which fic- tion survives. Some of these programs are now on the open television screen. New fiction releases from Ibero-America are also falling.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (corpus analysé); Argentine (lieu de production du savoir); _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Cinema in Expansion: Challenges and Promises of an Intercultural Relationship - Frey, Aline; Brito, Thaís (Canadian Journal of Film Studies, 2020)
Les auteures dressent le portrait tant des défis actuels que des possibilités qui naissent des relations interculturelles se tissant entre commissaires et cinéastes autochtones et non-autochtones dans le cadre du plus grand festival du film autochtone du Brésil, Cine Kurumin. Ce festival annuel, fondé en 2011, se déroule dans des villages ruraux autochtones, de même que dans des métropoles brésiliennes, attirant ainsi des auditoires variés. Le festival est ouvert aux cinéastes autochtones et non-autochtones qui produisent du matériel audiovisuel portant sur des sujets autochtones de partout dans le monde. Divers processus créatifs y sont encouragés grâce à l’organisation d’ateliers de scénarisation, et des partenariats établis avec des chaînes de télévision permettent une plus large diffusion des films sélectionnés. Alors que les productions audiovisuelles autochtones se développent, leurs contenus se diversifient ; elles englobent en effet de plus en plus de thèmes et de styles, de formats et de perspectives variées. En s’appuyant sur un cadre théorique postcolonial et décolonial, les auteures proposent de nouvelles perspectives sur un cinéma en pleine expansion ; les réalisateurs autochtones et leurs films circulent de plus en plus au sein de festivals non thématiques, reçoivent des prix et font rayonner leurs propres voix et points de vue auprès de publics variés, ce qui crée de nombreuses possibilités d’interactions et de dialogues interculturels. En outre, la mise sur pied de Cine Kurumin témoigne du pouvoir des productions audiovisuelles autochtones de générer des relations interculturelles entre cinéastes, commissaires et public.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Presencia negra en Bogotá: Décadas 1940-1950-1960
La exposición Presencia negra en Bogotá hace parte de la investigación en Migraciones que desde la Universidad Nacional lideran Mercedes Angola y Maguemati Wabgou. Está presente en el Claustro de San Agustín, como un homenaje a los hacedores de grandes historias que se desconocen, personas cuyos aportes a la construcción de la sociedad colombiana y a la consolidación de la identidad nacional desde diversas perspectivas y disciplinas ha invisibilizado la historia colombiana. En compañía de sus protagonistas, acompáñenos en la formulación de nuevas preguntas de investigación en torno al aporte de la gente negra a Colombia y a países vecinos, pues no solo se ha producido migración interna sino, "fuga" hacia otros países. Invitados : Mercedes Angola, artista plástica e investigadora y Maguemati Wabgou, sociólogo e investigador.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Cuerpos in/a-propiados: carte-de-visite y las nuevas ciudadanias en la pardocracia venezolana postindependentista - González-Stephan, Beatriz (Memoria y Sociedad, 2013)
En medio del proceso de construcción de la República, durante el siglo xix, en Venezuela los sectores no blancos de la sociedad intentaron legitimarse a través de la fotografía en las carte-de-visite, con el objetivo de ratificar su posición en esta sociedad ‘café con leche’. El uso de esta tecnología, así como la aparición y aceptación de manuales de urbanidad, fueron parte de un proceso en el que estos sectores intentaron ‘modernizarse’, reflejando las tensiones sociales asociadas, por ejemplo, a la dicotomía campo-ciudad o a la necesidad de ‘blanquearse’ ante los ojos de los coterráneos. El objetivo de este trabajo, es estudiar la manera en que el retrato fotográfico y el manual de urbanidad actúan en una sociedad cuyas diferencias y distancias sociales y económicas han sufrido un gran trastorno luego del proceso independentista. During the process of the construction of the Republic, in the 19th Century, non-white sectors of Venezuelan society attempted to legitimise themselves through photographs in their cart-de-visite, with the object of ratifying their position in this ‘coffee and milk’ society. The use of such technology, as well as the introduction and acceptance of urbanity handbooks, were part of a process in which these sectors tried to ‘modernise’, reflecting related social tensions, for example, the urban-rural dichotomy or the need for ‘whitening’ themselves in the eyes of their fellow citizens. The purpose of this paper is to study the way in which photographic portraits and urbanity handbooks act in a society in which social and economic differences and distances have undergone a great upheaval since the independence process.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Visionarias de la perspectiva de género en el arte contemporáneo del Caribe colombiano - Flórez, Alexa Cuesta (Memoria y Sociedad, 2017)
La perspectiva de género en el arte del Caribe colombiano se puede contextualizar con el movimiento feminista planetario. La comparación se establece en las creaciones de mujeres artistas de esta región, ya que subvierten, manifiestan y revelan con denotada libertad expresiva, no solamente sus inquietudes intimistas, sino toda una serie de cuestionamientos a las condiciones que culturalmente se le han impuesto a la mujer en el Caribe. Son dos generaciones diferentes; las primeras, analizadas en esta entrega, pueden ser catalogadas como pioneras de la perspectiva de género en el arte colombiano. Las segundas, consolidan problemáticas en apuestas individuales, de manera diaspórica y cada vez más comprometidas con el movimiento social de mujeres. En ambos casos lo hacen a través de las artes visuales, audiovisuales, performáticas e híbridas. Estamos ante artistas vanguardistas, de las artes visuales y performáticas en el Caribe colombiano; preferimos llamarlas, en ambos casos, visionarias. Gender perspective in the Colombian Caribbean art can be contextualized within the worldwide feminist movement. The comparison is established in the artwork of female artists from this region, as they subvert, demonstrate, and reveal with poignant expressive freedom, not only their intimate concerns, but a whole series of questions to the conditions that have been culturally imposed on women in the Caribbean. They come from two different generations. The first generation, analyzed in this installment, can be defined as the pioneers of gender perspective in Colombian art. The second generation consolidates issues through individual pledges in a diasporic way and increasingly committed to the social women’s movement. Both generations do this through performative, hybrid, visual and audiovisual art. These are avant-garde artists of the visual and performative art in the Colombian Caribbean. We prefer to call them, in both cases, visionaries.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Cuerpo, género y representación en el videoarte ecuatoriano (1998-2012) - Mantilla, Christian León (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2016)
Este texto reflexiona sobre los discursos e imaginarios de género y sexualidad que se producen dentro del campo del videoarte realizado en Ecuador entre 1998 y 2013. Desde finales de los noventa, hay una presencia de videos que abordan temáticas de cuerpo, política, deseo, violencia, roles e identidad que posicionan nuevos temáticas, lugares de enunciación y sujetos través de las tecnologías de video. A través de un conjunto de obras emblemáticas, el texto analiza los discursos y las estrategias visuales con las cuales se construyen feminidades, masculinidades y diversidades sexuales en el contexto contemporáneo. Está producción plantea un relato alternativo frente a las tendencias dominantes dentro de la historia del arte ecuatoriano. Muestra las nuevas sensibilidades y sujetos que se afirman a través del uso de tecnologías de video. This paper reflects on the speeches and imaginary of gender and sexuality that occur within the field of video art made in Ecuador between 1998 and 2013. Since the late nineties, there is a presence of vid-eos that address issues of body politics, desire, vio-lence, roles and identity that position new themes, places and subjects of enunciation through video technologies. Through a set of emblematic works, the text analyzes the speeches and visual strategies which femininity, masculinity and sexual diversities are built in a contemporary context. This production presents an alternative story against the dominant trends in the history of Ecuadorian art. It shows the new sensibilities and subjects that are affirmed through the use of video technology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Coloniality of Power, Eurocentrism, and Latin America - Quijano, Anibal (Nepantla: Views from South, 2000)
What is termed globalization is the culmination of a process that began with the constitution of America and colonial/modern Eurocentered capitalism as a new global power. One of the fundamental axes of this model of power is the social classification of the world’s population around the idea of race, a mental construction that expresses the basic experience of colonial domination and pervades the more important dimensions of global power, including its specific rationality: Eurocentrism. The racial axis has a colonial origin and character, but it has proven to be more durable and stable than the colonialism in whose matrix it was established. Therefore, the model of power that is globally hegemonic today presupposes an element of coloniality. In what follows, my primary aim is to open up some of the theoretically necessary questions about the implications of coloniality of power regarding the history of Latin America.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

La relación: pauta epistémica de la decolonialidad del saber desde el pensamiento afroantillano Los contornos del concepto en el Tratado del Todo-Mundo de Édouard Glissant (1928-2011) - Juncosa, José Enrique (Estudios Artísticos, 2016)
El presente artículo rastrea y explora el sentido poético y las posibilidades epistémicas del término relación a partir de la obra Tratado del todo-mundo, de Édouard Glissant, asumida como aporte del pensamiento afroantillano al proyecto del giro decolonial de los estudios interculturales latinoamericanos. En un primer momento, se identifican los rasgos y contornos operatorios de la identidad relación a partir de las siguientes claves de lectura: imaginería, poética y retórica, espiritualidad y ética, política y epistémica. En el segundo momento, se identifican las conexiones e implicaciones más relevantes para el contexto andino. De la exploración, se desprende que el pensamiento afrocaribeño de Glissant, contribuye a generar posibilidades discursivas potentes para enriquecer identidades abiertas en su diferencia y prácticas epistémicas sin amurallamientos identitarios o ilusiones uniformizantes. Finalmente, el aporte de Glissant, ofrece espacios de búsquedas a los movimientos sociales andinos para enriquecer sus prácticas de identidad en tanto relación, más allá de los esencialismos y la pretensión de raíz única. Cet article retrace et explore le sens poétique et les possibilités épistémiques du terme relation dans le traité d’Édouard Glissant, Traité du Tout-Monde, en tant que contribution afro-antillaise au projet du virage décolonial dans les études interculturelles latino-américains. Premièrement, nous identifions les traits et les contours opératoires de l›identité relationnelle à partir de clés suivantes : imagerie, poétique et rhétorique, spiritualité et éthique, politique et épistémique. Les liens les plus pertinents et les implications pour le contexte andin sont alors identifiés. De cette exploration, il est clair que la pensée afro-antillaise de Glissant contribue à générer de puissantes possibilités discursives pour enrichir des identités ouvertes dans leurs différences et leurs pratiques épistémiques, sans de murs identitaires ni d’illusions normalisatrices. Enfin, la contribution de Glissant ouvre des espaces de recherche pour les mouvements sociaux andins afin d’enrichir leurs pratiques d’identité en tant que relation, au-delà des essentialismes et de la prétention d’une seule origine.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Imaginarios y estrategias decoloniales - Ferrera-Balanquet, Raúl Moarquech (Estudios Artísticos, 2018)
Enunciando el delinking de la matriz moderna/ colonial, este artículo imagina un territorio crítico teórico creativo partiendo de la aesthesis decolonial con el fin de dialogar con una serie de hacedores culturales que emplean estrategias creativas decoloniales en proyectos creativos. Un acercamiento a la exposición Haceres Decoloniales (2015) realizada en Bogotá, ofrece la oportunidad de conversar sobre el hacer creativo de Benvenuto Chavajay, Rosa Tisoy Tandoy y Marco Alonso Roa. Los efectos de la colonialidad sonora conllevan a dialogar con la artista maya k´iche Sandra Monterroso y el creador maya yucateco Isaac Carrillo Can. Discursamos sobre el proyecto Espejo Negro (2010) de Pedro Lasch y el mural Las Aguas Sagradas de La Llorona (2004) de la artista xicana Juana Alicia. Terminamos con una interpretación crítica sobre el proyecto Mariposa Memoria Ancestral (2013-2015), y el performance multidisciplinario Whip It Good (2013) de la artista danesa trinitobaguense Jeannette Ehlers. En reliant la déconnexion de la matrice moderne / coloniale, cet article imagine un territoire créatif- théorique-critique à partir de l’aesthésis décoloniale, afin de dialoguer avec une série d’acteurs culturels qui utilisent des stratégies décoloniales créatives dans des projets créatifs. Une approche de l’exposition Haceres Decoloniales (2015) tenue à Bogotá, offre l’occasion de parler du travail créatif de Benvenuto Chavajay, Rosa Tisoy Tandoy et Marco Alonso Roa. Les effets de la colonialité sonore impliquent un dialogue avec l’artiste maya k’iche Sandra Monterroso et le créateur maya yucatècque Isaac Carrillo Can. Nous parlons du projet Espejo Negro (2010) de Pedro Lasch et de la peinture murale Las Aguas Sagradas de La Llorona (2004) de l’artiste chicane Juana Alicia. Nous terminons avec une interprétation critique du projet Mariposa Memoria Ancestral (2013-2015) et la performance pluridisciplinaire Whip It Good (2013) de l’artiste danois né en Trinité-et-Tobago Jeannette Ehlers.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Hacia una memoria decolonial: breves apuntes para indagar por el acontecimiento detrás del acontecimiento fotográfico - Schlenker, Alex (Revista de Investigación en el Campo del Arte, 2012)
El retrato ha sido, a lo largo de la historia de la fotografía, un ritual cuya gramática visual está siempre condicionada por una mirada determinada. Retratamos para recordar, para fijar un instante en el tiempo. Cuando recordamos lo fotografiado convocamos de nuevo ese instante, pero, además, convocamos una realidad, un orden social específico construido por determinados actores sociales. La fotografía ha representado y legitimado en muchos momentos un patrón de poder colonial que, a través de sus estructuras de dominación, ha elaborado rígidas jerarquías sociales y raciales que han circunscrito a indios, afros, mujeres y clases populares a lo que Frantz Fanon llama la zona del No-ser. ¿Es posible recordar, entonces, a partir de la fotografía, de manera crítica y sin reproducir en tal ejercicio la matriz colonial que hizo posible la toma de la imagen?
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Una lectura postpornográfica de Roberto Bolaño: escritura, feminismo y postcolonialismo - Rodríguez, Josué Hernández (Moderna språk, 2021)
The proliferation of critical and creative post-porn movements, which vindicate the representation of dissident sexualities under a new feminist, queer and transgender perspective, provide tools of analysis to rethink past literary and audiovisual pornographic productions, as well as to reformulate current ones. In this line of intermediate research, between cinema and literature, an approach to the work of Chilean writer Roberto Bolaño is proposed that will allow us to discern whether he can be considered a post-porn author related to the Golden Age of pornographic cinema in the 1970s and 1980s. Two of his stories and a novel will be studied: “Joanna Silvestri”, from which a gender reading will be made that problematizes the role of women within an eminently heteronormative industry, obsessed with representing male ejaculation; “Prefiguración de Lalo Cura”, analyzed under a postcolonial perspective of appropriation of subaltern bodies conceived as geographical territories, and Una novelita lumpen, in the field of porn pedagogy. The resulting findings make it possible to establish that Roberto Bolaño can indeed be considered a post-porn author by translating the narrative proposals of the Golden Age porn films into his own literary project, with a feminist and post-colonial critical intention.
Keywords: 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir)